Trait-based predation suitability offers insight into effects of changing prey communities - Benjamin Weigel; Erik Bonsdorff (PeerJ, 2018)
Increasing environmental pressures and human impacts are reshaping community structures and species interactions throughout all trophic levels. The morphological and behavioural characteristics of species communities contain key ecological information on why prey species appear attractive to predators but are rarely applied when exploring predator-prey (PP) relationships. Expanding our knowledge on how changing prey communities can alter the food resource suitability (RS) for predators is vital for understanding PP dynamics in changing ecosystems. Detailed predator diet data are commonly restricted to commercially important species and often not available over long temporal scales. To find out whether structural changes of prey communities impact the food RS for predator communities over space and time, we apply a novel framework to describe and interpret changes in predator diet-suitability based on predation-relevant traits of prey. We use information on described feeding links from the literature to compile the prey spectrum for each predator and subsequently translate the prey-species into a prey-trait spectrum. For each predator, we then calculate a frequency-based prey-trait affinity score and relate it to the available food resource pool, the community weighted means of prey traits, resulting in a prey-suitability measure. We aim to reveal whether a described multi-decadal change in the community structure of zoobenthos had an impact on the food suitability for the benthic-feeding fish in a coastal system of the Baltic Sea. We assess the direction of change in resource quality from the perspective of benthic-feeding fish and describe predator-specific responses to examine which species are likely to profit or be disadvantaged by changes in their prey spectrum. Furthermore, we test the relationship between functional diversity of prey communities and food suitability for predators, and whether predation linkage-structures are affected through prey community-changes. Our results show that changes in zoobenthic communities had a positive effect on the food suitability for most benthic-feeding fish, implying more suitable food resources. Species-specific responses of predators suggest varying plasticity to cope with prey assemblages of different trait compositions. Additionally, the functional diversity of zoobenthos had a positive effect on the food suitability for predator fish. The changing trait compositions of prey influenced the PP linkage-structure, indicating varying specialisation of benthic feeding fish towards available food resources. Our findings suggest that changing morphological characteristics of prey can impact food RS features for its predators. This approach enables long-term evaluation of prey quality characteristics where no detailed diet data is available and allows for cross-system comparison as it is not relying on taxonomic identities per se.